ROOSTER (HEN): FORM OF MYTHICAL CREATURES - БАЛЬСИС, Рімантас (Київський національний університет імені Тараса Шевченка, 2023)
This article is the continuation of the previous publications and reports given at scientific conferences that in one way or another, analysed the image of rooster/hen in the Baltic religion and mythology. This research aims to determine the relationship of the rooster/hen with various Lithuanian deities and mythical creatures and what reflections of this relationship can be encountered in the late 20th – early 21st century beliefs. The Catalogue of Lithuanian Narrative Folklore records quite a lot of sagas and beliefs in which a rooster / hen appears (is depicted) in the form of a rooster or a hen. Sagas in which household spirit appears in the form of a rooster are especially notable for their abundance. The image of the household spirit – rooster (household spirit is hatched from a rooster’s egg, fed with scrambled eggs, carries grain, lives in farm buildings, where grain is dried, threshed, and stored), brings it closer to the Lithuanian God of Threshing and Fire in the Threshing Barn called Gabjaujas. The idol of the god Vėjopatis, described by M. Pretorijus at the end of the 17th century and depicted with a rooster on his head, stands out for its originality. The available data allows the researchers to determine its purpose only hypothetically. Sagas and beliefs, in which fairies, devils, and witches assume the form of a hen (rarely, of a rooster), are considered of later origin when the images of the old faith were demonised under the influence of Christianity.

Представлена стаття є продовженням попередніх публікацій і доповідей автора на наукових конференціях, у яких, зокрема, йшлося про образ півня / курки в балтійській релігії та міфології. Метою розвідки є визначення зв’язку образу півня / курки з різними литовськими божествами та міфічними істотами, а також відображення цього зв’язку у віруваннях кінця XX – початку XXI століть. У Каталозі литовського оповідного фольклору зафіксовано досить багато саг і повір’їв, у яких півень / курка з’являється (зображується) в образі півня або курки. Особливою численністю вирізняються саги, у яких домовик постає в образі півня. Образ домовика – півня (він вилуплюється з півнячого яйця, годується яєчнею, носить зерно, живе в господарських будівлях, де сушать, молотять і зберігають зерно) зближує його з литовським богом молотьби і вогню в молотарці Габ’яуюсом. Оригінальністю вирізняється ідол бога Вейопатіса, описаний М. Преторіусом наприкінці XVII ст. і зображений з півнем на голові. Наявна інформація дає змогу дослідникам лише гіпотетично визначити його призначення. Саги та повір’я, у яких лісовики, чорти та відьми приймають образ курки (рідше – півня), вважаються такими, що мають пізніше походження, коли образи старої віри були демонізовані під впливом християнства.
ПІВЕНЬ (КУРКА): ФОРМА МІФІЧНИХ ІСТОТ
Keywords: півень; курка; міфічні істоти; саги; вірування; rooster; hen; mythical creatures; sagas; beliefs